2013
DOI: 10.1177/0894845313495587
|View full text |Cite
|
Sign up to set email alerts
|

Training and the Commitment of Outsourced Information Technologies’ Workers

Abstract: Outsourced workers in information technologies (IT) generally have high skills and a high value on the job market. Their IT outsourcing organizations are likely to provide them with training, in the first place for skill development, but perhaps also as a way to bind the workers to them. This can be understood along the role of the psychological contract. Outsourced IT workers may see training as a fulfillment of their psychological contract. Accordingly, we hypothesize that psychological contract fulfillment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 53 publications
4
22
0
Order By: Relevance
“…As Kraimer and colleagues (2011) suggested, raising PCO through policies such as job rotation and training may largely be a matter of letting employees learn more about the possibilities that are already available within the organization. Doing so could also embed employees within the organizations (Mitchell et al, 2001) or build mutual psychological contracts (Fontinha, Chambel, & De Cuyper, 2014; Ye, Cardon, & Rivera, 2012) or promote employees’ occupational commitment (Q. X. Weng & McElroy, 2012), especially for the highly employable employees.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%
“…As Kraimer and colleagues (2011) suggested, raising PCO through policies such as job rotation and training may largely be a matter of letting employees learn more about the possibilities that are already available within the organization. Doing so could also embed employees within the organizations (Mitchell et al, 2001) or build mutual psychological contracts (Fontinha, Chambel, & De Cuyper, 2014; Ye, Cardon, & Rivera, 2012) or promote employees’ occupational commitment (Q. X. Weng & McElroy, 2012), especially for the highly employable employees.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%
“…When workers perceive their psychological contract is honored by the employer, commitment is reflected in their attitudes, ultimately translating into more positive employee outcomes at workplace. Hence consistent with norm of reciprocity, higher contract fulfillment will results in higher commitment levels among employees and ultimately higher affective commitment contributes toward lower turnover intentions and higher constructive voice behaviors (Fontinha et al, 2014).…”
mentioning
confidence: 91%
“…Moreover affective commitment is considered valued indicator for positive organizational outcomes (Fontinha, Chambel, & Cuyper, 2014). Affective commitment has been emerged as the most significant dimension of organizational commitment in context of psychological contract as the extent to which the actual experience of a focal employee within the organization matched with his needs and expectation influence the level of affective commitment.…”
mentioning
confidence: 99%
“…A core element is the norm of reciprocity within the exchange relationship, which creates mutual obligations over time (Gouldner, 1960) and leads to the expectation that each party will fulfill its commitments (Aselage & Eisenberger, 2003; Blau, 1964). Thus, previous research has confirmed that employees respond with positive reactions, such as job satisfaction and commitment, when employers keep their promises (de Jong et al, 2009; Fontinha et al, 2014). Furthermore, Coyle‐Shapiro and Kessler (2002) provided support for reciprocity, suggesting that perceived fulfillment of one party's obligations at Time 1 was positively related to perceived fulfillment of the other party's obligations at Time 2.…”
Section: Introductionmentioning
confidence: 81%